(3eLdI GdeLeY GdYdej GdgfOj (B/s - (3LGeYI YdjcQI GdESdGejI s (3GdeLeY GdYdej GdgfOj (B((3GdgfO(B)s ((3GdgfO (B:s (3GdeLeY GdYdej GdgfOj,s, 1976)
(3aj GddZI GdYQHjI hGdCOH(B.s
(3WQjbI GdhUhd (B: (3THcI GdEfJQfJ(B.s
(3JGQjN GdGWdGY (B: 24 / 3 / 2021.s
(3BNQ YOO Je JOGhdg (B: (3GdeLdO (B21(3, GdYOO (B1(3, (B2 (1420-1421 (3g`(B. = 2000-2001)s
Keywords: (3GddZI GdYQHjIs -- (3OhQjGJs; (3GdCOHs -- (3OhQjGJs